Accelerated Algorithm of Least-Sguares Approximation of Signals by Exponentials for Wideband Frequency-Domain Reflectometry - Andreev, M. V.; Drobakhin, O. O.; Demyantchuk, K. A. (Видавничий дім «Академперіодика», 2013)
Accelerated Algorithm of Least-Sguares Approximation of Signals by Exponentials for Wideband Frequency-Domain Reflectometry